Hypromellose-based films and film-forming systems for topical application: current status and perspective in drug delivery - Milinković, Sandra; Djekić, Ljiljana (Archives of Pharmacy, 2024)
Films and film-forming systems (FFS) are increasingly recognized for their potential as convenient carriers for precise and efficient drug delivery to or via the skin and mucous membranes. Among them, those based on hypromellose as a film-forming polymer demonstrate many favorable characteristics. To better understand the role of hypromellose in topical films and film-forming drug delivery systems, this review presents physicochemical characteristics and film-forming performances of different types of hypromellose. Furthermore, the review encompasses relevant studies demonstrating the broad application of hypromellose as a film-forming agent in films and FFS for dermal, oromucosal, vaginal, ocular, and nasal application, reflecting the growing interest of researchers in this field. It also highlights the observed advantages of hypromellose over other film-forming polymers and implies future development of films and FFS in general.
Keywords: film; film-forming systems; drug delivery; hypromellose; topical application